23.4k views
4 votes
The following steps are used to rewrite the polynomial expression (x+4y+z)(x-7y)

User BlackPearl
by
6.2k points

2 Answers

6 votes
(x+4y+z)(x-7y)=
x^(2) +4xy+xz-7xy-28y-7yz
=
x^(2) -3xy+xz-7yz
User UserFog
by
6.5k points
4 votes

Answer:

The product
\left(x+4y+z\right)\left(x-7y\right)=x^2-3xy-28y^2+xz-7yz

Explanation:

Given expression (x+4y+z) and (x-7y)

We have to find the product of given expression that is
\left(x+4y+z\right)\left(x-7y\right)

Consider
\left(x+4y+z\right)\left(x-7y\right)

First multiply each term of first bracket with each term of second bracket, we have,


=xx+x\left(-7y\right)+4yx+4y\left(-7y\right)+zx+z\left(-7y\right)

Apply plus- minus rule,
-(-a)=a , we have,


=xx-7xy+4xy-4\cdot \:7yy+xz-7yz

Like terms are terms with same variable having same power.

Adding like terms , we have,


=xx-3xy-4\cdot \:7yy+xz-7yz

Simplify, we have,


=x^2-3xy-28y^2+xz-7yz

Thus, the product
\left(x+4y+z\right)\left(x-7y\right)=x^2-3xy-28y^2+xz-7yz

User Ethanpil
by
6.2k points